Effect of Digital Marketing Capabilities and Blockchain Technology on Organizational Performance and Psychology - Liu, Ying (Frontiers in Psychology, 2022)
Digitalization plays an integral role in the transformation of the Omni structure. The current study aims to investigate the effect of digital marketing capabilities (DMCs) and blockchain technology on customer-linking capabilities (CLCs), market-sensing capabilities (MSCs), consumer-brand engagement (CBE), and firm performance in China. The study is quantitative, and a simple random sampling technique was adopted for data collection. Data has been accumulated through a structured questionnaire while distributing 311 questionnaires, and a 5-point Likert scale was used to collect the data from the respondents employed in the Omni structure industries. The research hypothesis was tested by using the structural equation modelling (SEM) technique. The results have identified a significant correlation and direct effect between DMCs, CLCs, MSCs, and firm performance. Remarkably, the effect of DMCs on CBE is significant. The mediating effect of MSCs and CLCs is significant between the relationship of DMCs and a firm’s performance. The organization performance in the Omni structure depends on how well the DMCs have been employed. DMCs influence MSCs, CLCs, and CBE. Henceforth, the current study contributes by analyzing the role of DMCs in blockchain technology.